Effect of restricted feed intake on finishing pigs weighing between 150 and 250 lb fed twice or six times daily - J D Schneider; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
Two 42-d trials and two 28-d trials were conducted to evaluate the effects of restricted feed intake and feeding frequency (2 or 6 times daily) on the performance of pigs weighing between 150 to 250 lb (initially 148 lb in Exp. 1; 155 lb in Exp. 2; 156 lb in Exp. 3; and 156 lb in Exp. 4). In all experiments, pigs were housed in 6 × 10 ft pens with half-solid concrete and half-slatted flooring and with one nipple waterer. Pigs were fed a corn-soybean meal-based diet formulated to 1.15% TID lysine and 1,491 kcal of ME/lb. In Exp. 1 to 3, energy and lysine were supplied to pigs to target an average growth rate of 1.75 lb/d based on NRC (1998) values. In Exp. 4, the diet was supplied to pigs to target growth rates of 1.75 lb/d (low feed intake) or 2.1 lb/d (high feed intake) based on NRC (1998) values to determine if the amount of energy above maintenance and feeding frequency has an effect on performance. Pigs were fed by dropping similar daily amounts of feed, either 2 (0700 and 1400) or 6 times (3 meals within 2 h at AM and PM feedings) per day, by an Accu-Drop Feed DispenserÂ® on the solid concrete flooring. In Exp. 1 and 2, increasing the feeding frequency of pigs fed a restricted diet from 2 to 6 times per day improved (P<0.02) ADG and F/G. Increasing the feeding frequency increased (P<0.05) the duration of time spent feeding and standing, and reduced lying time. In Exp. 3, a third treatment was included in addition to those used in Exp. 1 and 2 to determine whether the improvements in performance were due to decreased feed wastage. This treatment was designed to minimize feed wastage by dropping feed closer to the floor in pigs fed 2 times per day. Like Exp. 1 and 2, pigs fed 6 times per day had improved (P<0.05) ADG and F/G compared to either treatment fed 2 times per day. There was no difference (P>0.05) in performance between pigs fed 2 times per day when feed was dropped from the feed drop or by the modified method. In Exp. 4, increasing the feeding frequency from 2 to 6 feeding periods improved (P<0.01) ADG and F/G for pigs fed a low level of feed intake and tended to increase (P<0.06) ADG and improve (P<0.05) F/G for pigs fed a high level of feed intake. In conclusion, these studies indicate that increasing the frequency of feeding from 2 to 6 times a day improves pig performance compared with feeding 2 times per day.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; Feed management; Restricted intake